2003
DOI: 10.1002/pola.10842
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐metal‐templated synthesis of rotaxanes and catenanes: From small molecules to polymers

Abstract: This article provides an overview of the fundamental principles of the synthesis of metallocatenanes and metallorotaxanes. It also describes the synthesis and properties of electronic conducting polymers—polypyrrole and polythiophene—built around metallocatenanes and metallorotaxanes. The particular properties of this new class of polymers, including the possibility of transmetallation reactions being performed with them and the observation of electronic coupling between the metal centers and the conducting ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…But most of them have given stress on different types of preparation technique and characterization of the composites. But very few of them describe the systematic study of temperature variation of electrical conductivity and also the magnetic field dependence of electrical conductivity [36][37][38][39][40][41][42]. Sahoo et al [39] studied the room temperature conductivity of the PPy-MWCNT composites and concluded that the conductivity of the composites was increased by one order of magnitude than pure polypyrrole.…”
Section: Introductionmentioning
confidence: 99%
“…But most of them have given stress on different types of preparation technique and characterization of the composites. But very few of them describe the systematic study of temperature variation of electrical conductivity and also the magnetic field dependence of electrical conductivity [36][37][38][39][40][41][42]. Sahoo et al [39] studied the room temperature conductivity of the PPy-MWCNT composites and concluded that the conductivity of the composites was increased by one order of magnitude than pure polypyrrole.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, bithiophene-bipyridine and bithiophene-phenanthroline monomers (Scheme 2) have been prepared and used for templatesynthesis of rotaxane monomers with phenanthroline macrocyclic compounds [36][37][38][39] In the first case, heteroaromatic ring has the polymerisable positions sterically blocked by macrocycle walls and polymerisation is impossible, while for the second case these positions are more accessible.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, a new class of conjugated materials with novel electronic and electrochemical characteristics was obtained by the hybridization of ICPs with transition metal complexes [211][212][213]. The cooperative behavior between a large number of photonic and electronic properties of metallic centers and the conjugated matrix can be achieved by forcing the π-conjugation to go through a metallic center or by an electronic coupling via the metal-ligand orbitals.…”
Section: Electropolymerization As a Tool To Elaborate Functional Conjmentioning
confidence: 99%